Basic education teacher training policies in Brazil and in Portugal (2014-2023) – convergences and divergences (Research, Society and Development, 2024)
The outcomes of a post-doctoral research conducted at the University of Minho in Braga, Portugal, are here socialized and presented. The purpose of this study was to compare and contrast the initial years of Basic Education policy for teacher training in Brazil and in Portugal (2014–2023). The methodology used was a qualitative one with a literature review, a documentary and empirical analysis which were conducted through interviews with eight teacher trainers from two universities who have more than fifteen years of experience in teacher training: UFU (Brasil) and UMinho (Portugal). The findings emphasized the similarities in training programs in both nations, including the impact of neoliberalism, the devaluation of educators, the contradiction between theory and reality and the limits of the democratic process in making policy. Different from Brazil, the Portuguese training program gives two extra years as a professional master's degree in various forms and three common years for a bachelor's degree. Portugal has different standards in the areas of career induction, research methods, pedagogical practice and educational sciences. Among other things, the two countries' conceptions of public universities are different. Both nations must, however, enhance their policies and procedures for teacher training concerning the current barriers to attaining higher-quality education.